2022
DOI: 10.3390/ani12243528
|View full text |Cite
|
Sign up to set email alerts
|

GPX2 Gene Affects Feed Efficiency of Pigs by Inhibiting Fat Deposition and Promoting Muscle Development

Abstract: GPX2 has been recognized as a potential candidate gene for feed efficiency in pigs. This article aimed to elucidate polymorphism of GPX2 associated with feed efficiency and its related molecular mechanism. In this study, seven single nucleotide polymorphisms (SNP) of GPX2 were found among 383 Duroc pigs. In addition, seven SNPs and ALGA0043483 (PorcineSNP60 BeadChip data in 600 Duroc pigs), which are near the GPX2 gene, were identified in one haplotypes block. Furthermore, associated studies showed that the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In mammals, liver and adipose tissue serve as the main sites of lipid synthesis; e.g., in pigs, fatty acid synthesis occurs mainly in adipose tissue, whereas, in chickens, liver tissue is the major organ for lipid de novo synthesis [49][50][51][52]. Excessive fat deposition reduces feed remuneration and restricts the development of the poultry industry to a certain extent [53]. We found that the STC2 gene was specifically highly expressed in chicken liver tissues.…”
Section: Discussionmentioning
confidence: 80%
“…In mammals, liver and adipose tissue serve as the main sites of lipid synthesis; e.g., in pigs, fatty acid synthesis occurs mainly in adipose tissue, whereas, in chickens, liver tissue is the major organ for lipid de novo synthesis [49][50][51][52]. Excessive fat deposition reduces feed remuneration and restricts the development of the poultry industry to a certain extent [53]. We found that the STC2 gene was specifically highly expressed in chicken liver tissues.…”
Section: Discussionmentioning
confidence: 80%
“…Numerous studies have demonstrated the ability of GPX2 to control cell division and proliferation [ 10 , 12 , 13 ]. However, the majority of GPX2 cell proliferation research being done now focuses on cancer and other issues [ 14 , 15 ], and the effects on porcine adipocytes and skeletal muscle cells have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To put it briefly, GPX2 encourages the growth of muscle and prevents the accumulation of fat. Furthermore, our earlier research discovered that the combination genotype G3 increased the expression of GPX2 in several organs [ 10 ]. Thus, selecting people with high GPX2 genes may be accomplished by using genetic approaches to identify the SNPs boosting GPX2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation